1995
DOI: 10.1021/bi00007a030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions of 3',5'-Cyclic Purine Analogs with the Binding Site of Retinal Rod Ion Channels

Abstract: Photoreceptor outer segments transduce information about incoming light levels through a class of ion channels that respond directly to changes in cytosolic 3',5'-cyclic guanosine monophosphate levels. A series of 3',5'-cyclic purine analogues with alterations at N1, C2, C6, or C8 positions was used to examine molecular interactions between the nucleotide and the channel. The maximal current activated by C2-altered analogues in excised membrane patches was less than the current activated by cGMP, and the K0.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…1) Substitutions at the C-8 position of the purine ring increase bulkiness and shift the conformational equilibrium toward the syn-form (19,39,47,48). If cGMP bound to the noncatalytic sites in the syn-conformation, it would be expected that 8-substituted analogs might show increased binding affinity compared with cGMP, as has been observed for the binding sites of the cyclic nucleotide-gated ion channel (16,18,19) and the cGMP-dependent protein kinase (15). In both of these proteins, cGMP is believed to occupy the binding site in the syn-conformation (18,49,50).…”
Section: Table II Substitutions In the C-2/n-3 Region Of The Purine Ringmentioning
confidence: 94%
See 2 more Smart Citations
“…1) Substitutions at the C-8 position of the purine ring increase bulkiness and shift the conformational equilibrium toward the syn-form (19,39,47,48). If cGMP bound to the noncatalytic sites in the syn-conformation, it would be expected that 8-substituted analogs might show increased binding affinity compared with cGMP, as has been observed for the binding sites of the cyclic nucleotide-gated ion channel (16,18,19) and the cGMP-dependent protein kinase (15). In both of these proteins, cGMP is believed to occupy the binding site in the syn-conformation (18,49,50).…”
Section: Table II Substitutions In the C-2/n-3 Region Of The Purine Ringmentioning
confidence: 94%
“…If cGMP bound to the noncatalytic sites in the syn-conformation, it would be expected that 8-substituted analogs might show increased binding affinity compared with cGMP, as has been observed for the binding sites of the cyclic nucleotide-gated ion channel (16,18,19) and the cGMP-dependent protein kinase (15). In both of these proteins, cGMP is believed to occupy the binding site in the syn-conformation (18,49,50). Instead, almost all substitutions at the C-8 position substantially reduce the binding affinity of cGMP analogs to the PDE noncatalytic sites (Table III), consistent with an anti-conformation of cGMP in the binding pocket.…”
Section: Table II Substitutions In the C-2/n-3 Region Of The Purine Ringmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies using nucleotide analogs have shown that the binding domain is remarkably tolerant of changes in the purine ring substituents. Analogs with a thio substituent as 6-thio-cGMP, a monobutyryl as N 6 -monobutyryl cAMP, or rings as 1-N 6 -etheno cAMP (Scott and Tanaka, 1995;Tanaka et al, 1989) and PET-cGMP (Wei et al, 1996), all activate currents in rod channels. Due to this tolerance for changes in both size and charge at various positions on the purine, the most interesting analogs are those that fail to activate CNG channels.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the only inactive purine-modified analogs identified to date are modified at the C 6 or N 1 positions. Two of these analogs have single atom changes: 2-aminopurine riboside 3Ј-5Ј-monophosphate (2-amino-cPNP), which has a hydrogen in place of the oxygen of cGMP at C 6 (Tanaka et al, 1989), and N 1 -oxide cAMP with an oxygen instead of hydrogen at the N 1 position (Scott and Tanaka, 1995). Neither analog binds to rod channels, as shown by cGMP competition studies.…”
Section: Introductionmentioning
confidence: 99%